Perspectives on Collaboration between Physicians and Nurse Practitioners in Japan: A Cross-Sectional Study - Mari Igarashi; Ryuichi Ohta; Akinori Nakata; Yasuo Kurita; Yuta Mitobe; Miho Hayakawa; Tsutomu Yamazaki; Harumi Gomi (MDPI AG, 2022)
Background: Nurse practitioners (NPs) are known as effective healthcare providers worldwide. In Japan, nurse practitioner adoption is considered to be in a shaky period. Although nurse practitioners were introduced approximately 10 years ago at the initiative of educational institutions in Japan, the full extent of this trend is not known. Therefore, we have clarified the whole picture of nurse practitioners from two directions: the perception of nurse practitioners in Japan and the perception of physicians who work with nurse practitioners. This will inform discussions regarding the recruitment of nurse practitioners at the national level in Japan. Methods: From 18 June to 24 July 2021, we administered a nationwide cross-sectional survey of NPs and physicians working in the same clinical settings as NPs in Japan. The domains of the survey included "scope and content of work", "perceptions of NPs' clinical practice", and "individual clinical practice characteristics". The survey was distributed and collected digitally. Results: The total number of respondents to the survey was 281, including 169 NPs and 112 physicians; the percentage of NPs who responded was 50.5%. The number of valid responses was 164 NPs and 111 physicians, for a total of 275 respondents. Approximately 60% of NPs are concentrated in Tokyo, the capital of Japan, and the three prefectures adjacent to Tokyo. They also worked fewer hours per week, cared for fewer patients per day, and earned less money than physicians. More physicians than NPs indicated that "more NPs would improve the quality of care". A total of 90.1% of physicians and 82.3% of NPs agreed that "Nurse practitioners should practice to the full extent of their education and training," and 73.9% of physicians and 81.7% of NPs agreed that "Nurse practitioners' scope of practice should be uniformly defined at a national level". Conclusions: This study clarified the present working conditions of NPs from NPs' and physicians' perspectives in Japanese contexts. Japanese NPs may be able to work effectively in collaboration with physicians. Therefore, the implementation of NPs in Japanese medical conditions should be discussed further for better healthcare.